Rencontres entre philosophie des sciences, philosophie de la technologie et STS - Juan Carlos Moreno; Dominique Vinck (Revue d'anthropologie des connaissances)
The relations between the philosophy of science, the philosophy of technology and the field of STS have been very broad and diverse over five decades, although distancing, controversies and disputes have prevailed. However, the analysis of the approaches made from philosophy to STS studies shows that a new scenario of novel and constructive encounters between these fields has emerged, after the influence of the science wars debates, in some specific philosophical perspectives on science and technology, unfortunately still little known. These include: studies of experimentation, the practical turn in the philosophy of science, the development of historical epistemology, the empirical turn in the philosophy of technology, and the approach to the moral relevance of artefacts. The analysis of the encounters between the aforementioned philosophical perspectives and the STS field can serve to stimulate and invite the development of other possible encounters such as those presented in this thematic dossier.